Care of HIV-Infected Pregnant Women in Maternal-Fetal Medicine Programs - Peter A. Sklar; Susanne L. Bathgate; Heather A. Young; David M. Parenti (Hindawi Limited, 2001)
Objective: To survey the evolution over the past decade of attitudes and practices of obstetricians in maternal-fetal medicine fellowship programs regarding the management of human immunodeficiency virus (HIV)-infected pregnant women.